Contribution of marginal non-crop vegetation and semi-natural habitats to the regulation of insect pest populations by their natural enemies - Santos, Luan Alberto Odorizzi dos [UNESP] (2017)
The expansion of agricultural areas has led to the loss of biodiversity due to the reduction of natural and semi-natural habitats in agricultural landscapes. With the increase of agricultural production in the world, environmentally sound techniques are increasingly discussed that allow a sustainable management of surrounding habitats. The effects of these habitats on the population of insect pests and their natural enemies are still poorly understood. The objective of this thesis was to understand the effects of natural and semi-natural environments on the population of insect pests and natural enemies in tropical (Brazil) and temperate (France) regions. In Brazil (Chapter II) the effect of the distance of fragments on the population of predatory and omnivorous ants in sugarcane was evaluated. The results showed that the species richness decrease with distance from forest fragments and that the dominance of the species Dorymyrmex bruneus and Pheidole oxyops increase. Ant species colonizing sugarcane fields were also found in forest fragments suggesting that the latter habitats are refuges for predatory ant species during periods of disturbance such as sugarcane harvest or soil tillage. This was confirmed by stronger differences in ant communities after sugarcane harvest (dry season) than four months later (rainy season) when absence of disturbance allowed re-colonosiation by ants. There was also a difference in the richness of ant species between different fragment types (river valleys and plateaus). In France, the effect of wildflower strips, spontaneous vegetation and grass strips on the community of natural enemies and the regulation of the rosy apple aphid Dysaphis plantaginaea (Chapter III) were evaluated. Concerning major natural enemies, our results showed a higher density of hoverflies in wild flower strips compared with other strip types but no differences for ladybirds (coccinelidae). However, no differences in natural enemy densities were observed inside orchards. Aphid number was higher close to the margins suggesting that colonization from margin strips may counteract positive regulatory effects of natural enemies. Positive effects of strip margin vegetation on regulation of apple pests require a movement of natural enemies into the orchard. We tested the movements of generalist predators by labelling margin strips with egg protein and we checked whether they fed on pest insects using specific genetic marker of the codling moth (Cydia pomonella) (chapter IV). The results showed that few individuals were moving from the field margins into the orchard. However, 25% of the captured predators fed on C. pomonella still indicating a high level of natural regulation. In conclusion, the limited movement of predators from margin strips into orchards may explain the absence of differences between strip treatments in orchard pest regulation (aphids). Natural and semi-natural habitats can contribute to pest control at the margins of crops, but in apple orchards this effect strongly decreased with distance.